2020
DOI: 10.1016/j.bjps.2020.02.033
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of tarsal tunnel syndrome in diabetic subjects

Abstract: Introduction: Tibial nerve entrapment is highly prevalent in diabetic subjects, resulting in significantly more neuropathic complaints and concomitant sensory disturbances. The study aim was to assess the impact of tarsal tunnel syndrome (TTS) and sensory loss at baseline on incident diabetic foot ulceration (DFU) in diabetic patients, since decompressing the tibial nerve might change the natural history of the disease. Methods: In this study, 113 subjects with TTS (69 bilateral, 23 left-sided and 21 right-sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Identified medical conditions include hypothyroidism, diabetes mellitus, systemic sclerosis, chronic renal failure. 4,7,[15][16][17][18][19][20][21] The myxedema that occurs in hypothyroidism can lead to tarsal tunnel syndrome from the increased swelling of tissues in the tarsal tunnel. 17 Patients affected by diabetes mellitus have higher rates of tarsal tunnel syndrome due to the chronic compression of the posterior tibial nerve which can further lead to diabetic foot ulceration.…”
Section: Orthopedic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identified medical conditions include hypothyroidism, diabetes mellitus, systemic sclerosis, chronic renal failure. 4,7,[15][16][17][18][19][20][21] The myxedema that occurs in hypothyroidism can lead to tarsal tunnel syndrome from the increased swelling of tissues in the tarsal tunnel. 17 Patients affected by diabetes mellitus have higher rates of tarsal tunnel syndrome due to the chronic compression of the posterior tibial nerve which can further lead to diabetic foot ulceration.…”
Section: Orthopedic Reviewsmentioning
confidence: 99%
“…17 Patients affected by diabetes mellitus have higher rates of tarsal tunnel syndrome due to the chronic compression of the posterior tibial nerve which can further lead to diabetic foot ulceration. 18,19 Hemodialysis patients were found to have tarsal tunnel syndrome with rates up to 0.5% with increasing prevalence as maintenance dialysis went beyond 5 years most likely due to the deposition of beta-2 microglobulin. 21…”
Section: Orthopedic Reviewsmentioning
confidence: 99%
“…[18][19][20] The test grades the level of somatosensory function in the distal lower extremity and relates to postural stability, risk of falls, risk of ulceration, and surgical outcome of LEND surgery. 18,[21][22][23] The Tinel sign was used for the diagnosis of lower extremity peripheral nerve entrapment. 24 Lower extremity artery pulsations were palpated.…”
Section: The Rotterdam Diabetic Foot Study Test Batterymentioning
confidence: 99%
“…They evaluated the impact of TTS and initial sensory loss on DFU, given tibial nerve decompression could change the natural history of the disease (preventing diabetic foot disease and thus reducing the risk of amputation). 59 It was observed that bilaterally affected patients have a poorer evolution compared to unilateral patients and controls, and they have a higher risk of developing DFU than unilateral patients. Thus, it appears that surgical decompression of the tarsal tunnel in diabetic patients with TTS might decrease the risk of developing DFU.…”
Section: Prognosismentioning
confidence: 99%